Mg Substitution Clarifies the Reaction Mechanism of Olivine LiFePO4. Issue 7 (12th December 2014) - Omenya, Fredrick; Wen, Bohua; Fang, Jin; Zhang, Ruibo; Wang, Qi; Chernova, Natasha A.; Schneider‐Haefner, Joe; Cosandey, Frederic; Whittingham, M. Stanley
<x xml:space="preserve">Abstract</x> Understanding the reaction mechanism of olivine compounds as electrode materials for lithium lithium‐ion batteries have has received much attention recently. The question whether olivine LiFePO4 undergoes two‐phase or non‐nonequilibrium single‐phase reaction during electrochemical processes has taken center stage in the understanding of the faster reaction kinetics observed in this material. Here, the lithiation/delithiation mechanism of Mg Mg‐substituted LiFePO4 using high high‐resolution X‐ray diffraction(XRD), transmission electron microscopy(TEM), and electrochemical measurements is reported. Ex situ partially (de)lithiated olivine‐ LiMg0.2Fe0.8PO4 show the existence of stable equilibrium intermediate phases as characterized by the presence of more than two phases and broadness of diffraction peaks. Electron energy loss spectroscopy profiles across individual nanoparticles further confirm uniform lithiation with a constant Fe–L3 energy measured across each nanoparticle, suggestive of solid solution behavior in individual particles. In addition, a continuous shift in the diffraction peak position is observed even in the "two‐phase" region in the ex situ electrochemical (de)lithiated electrodes.